The employment effect of deregulating shopping hours: Evidence from German retailing - Mario Bossler; Michael Oberfichtner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2014)
We provide difference-in-differences evidence from Germany on the effect of deregulating weekday shop opening hours on employment in food retailing. Using data on the universe of German shops, we find that relaxing restrictions on business hours increased employment by 0.4 workers per shop corresponding to an aggregate employment effect of 3 to 4 per cent. The effect was driven by an increase in parttime employment while full-time employment was not affected. The statistical significance of these results hinges on assumptions on error correlation, and we hence report inference robust to clustering at different levels. A back-of-the-envelope calculation gives an employment increase by 0.1 workers per additional actual weekly opening hour. – – Wir untersuchen den Effekt der Freigabe der Ladenöffnungszeiten auf die Beschäftigung im deutschen Lebensmitteleinzelhandel mit der Differenz-von-Differenzen-Methode. Unter Verwendung von Daten über alle deutschen Einzelhändler finden wir, dass die Ausweitung der gesetzlich erlaubten Ladenöffnungszeiten die Beschäftigung um durchschnittlich 0,4 Arbeitnehmer pro Laden erhöht hat, was einer Zunahme der Beschäftigung um 3 bis 4 Prozent entspricht. Getrieben wird dieser Effekt von einer Zunahme der Teilzeitbeschäftigung, wohingegen die Vollzeitbeschäftigung nicht betroffen war. Die statistische Signifikanz der gefundenen Effekte hängt von den Annahmen an die Störtermkorrelation ab und wir berichten daher Ergebnisse bei Clustering auf verschiedenen Ebenen. Eine Überschlagsrechnung zeigt eine Zunahme der Beschäftigung um 0,1 Arbeitnehmer pro Erhöhung der tatsächlichen wöchentlichen Öffnungszeiten um eine Stunde.
Keywords: J23; L51; L81; 330; shop opening regulations; employment; retail sector; Germany